Strategic Planning and Digital Engagement: A Theoretical Analysis of Marketing Communication on Instagram (A Case Study of @setangkaiproject) - Laksono, Prabowo Adi; Hariyanto, Fajar; Ramdhani, Muhamad (Universitas Dharmawangsa Medan, 2026)
This study aims to explore the marketing communication strategy implemented by the photography service account @setangkaiproject through Instagram. Using a qualitative phenomenological approach based on Edmund Husserl's framework and analyzed through Planning Theory and the Circular Model of SoMe, this research reveals the strategic planning, implementation, and evaluation processes in digital marketing communication. Data were collected through in-depth interviews with account managers and thematic analysis of Instagram content. The findings indicate that @setangkaiproject's strategy is systematically organized, structured, and consistently implemented. Content planning is conducted through theme development, visual concepts, and color tones aligned with brand identity. Strategy implementation follows the four stages of the Circular Model of SoMe: Share, Optimize, Manage, and Engage. Evaluation based on Instagram insights is used to assess content effectiveness and adjust subsequent strategies. This study concludes that the designed communication strategy successfully supports the formation of a professional image and increases audience interaction and interest in @setangkaiproject's photography services.